Wild and Valuable? Tourist Values for Orang-utan Conservation in Sarawak - Kerstin K, Zander; Sing Tyan, Pang; Christina, Jinam; Andrew Alek, Tuen; Stephen T, Garnett (Medknow Publications, 2014)
Fluffy, orange and endearing, orang-utans have won the hearts of people all over the world. However, all sub-species are endangered in the wild with the Bornean orang-utan population having declined by more than 50% over the past 60 years. Fewer than 2,000 wild orang-utans remain in Sarawak with nearly all truly wild ones confined to a remote site on the Indonesian border. Yet each year thousands of tourists and local Sarawak people see orang-utans semi-wild in a reserve or captive in a rehabilitation centre.